On localized deformation and recrystallization as damage mechanisms during thermomechanical fatigue of single crystal nickel-based superalloys - Moverare, J; Sato, A; Johansson, S; Hasselqvist, M; Reed, R; Kanesund, J; Simonsson, K (2011)
Thermomechanical fatigue (TMF) in superalloys is growing in importance due to the introduction of advanced cooling systems but also due to the changes in demand and competition within the power generation market; this is requiring many power plants to operate under cyclic conditions. In this paper the TMF behaviour of three different single crystal nickel-based superalloys are compared. It is demonstrated that the deformation and damage mechanisms occurring during TMF are rather different from those traditionally reported for creep or isothermal fatigue. In all cases examined, the deformation is localized within a rather small number of deformation bands. While these bands were found to consist mainly of micro-twins in some alloys, in others they might be better described as slip or shear bands. Furthermore, in some circumstances these bands are prone to recrystallization. In CMSX-4, the intersection points of twins of different orientation act as initiation sites for this process. In the SCA425 alloy - of smaller gamma' content, lower creep resistance and less great oxidation resistance - twinning is observed infrequently; however the deformation is still very localized and in the distorted gamma-gamma' microstructure, along the shear bands, recrystallization is observed. Furthermore the recrystallization is enhanced by oxidation due to the development of a gamma'-depleted zone. In CMSX-4, TCP phases precipitated during long term ageing cause a more dispersed deformation behaviour which prevents recrystallization. Our findings confirm the importance of an inhomogeneous microstructure for good TMF resistance. © (2011) Trans Tech Publications Switzerland.